Effects of a training session on IGF-I, IGFBP3, CK and LDH of brazilian jiu-jitsu fighters - Tourinho Filho, H.; Puggina, E. F.; de Moraes, C.; de P. Oliveira, L.; Pires, M.; Martinelli Junior, C. E. (Journal of Combat Sports and Martial Arts, 2016)
Introduction. Exercise is related to anabolism induced by the GH/IGF-I axis, which is responsive to high intensity training. However, the literature is ambiguous regarding the behavior of the GH/IGF-I axis during exercise. While some studies shows increased levels of these hormones, other studies have found reduced levels of IGF-I after training sessions. From these statements, the objectives of this study were to investigate the effects of a Jiu-Jitsu training session on the IGF-I, IGFBP-3, CK and LDH concentrations. Material and methods. Nine male jiu-jitsu fighters participated in the study, they represent the national elite of the sport in Brazil, with 5.4±2.7 years of practice. Blood samples were collected in the beginning and at the end of a training session. IGF-I, IGFBP3, CK and LDH were assayed by colorimetric methods. Results. were analyzed using Wilcoxon test (p< 0.05). Results: No difference was observed regarding IGF-I (p= 0.57) and IGFBP-3 (p= 0.73) levels before and after the Jiu-Jitsu training session. A jiu-jitsu training session composed by six fights of 7.5 minutes with perception of effort between "hard" and "very hard" did not change the IGF- I and IGFBP-3 concentrations. Regarding CK activity, increases were observed (p= 0.002) when comparing the situations before and after training session, while LDH enzyme activity was not affected (p= 0.80). Conclusions. The absence of reduced values of IGF-I and IGFBP-3 in the second measurement would be explained by the training status of the athletes, who were in their maximum level of performance in the season.